Periligature Injuries in Hanging - A Taciturn Proof (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Hanging is a common suicidal option and careful observation and documentation of ligature mark is an important aspect during medicolegal postmortem. Apart from ligature mark found in hang ing some other injuries such as rope burn, bruise, nailmarks etc. seen around ligature mark known as ‘periligature injuries’. A prospective study of 80 cases was done in regard to these periligature injuries and its importance highlighted.
Keywords: Hanging; Periligature injury; rope burn; abrasion; ecchymosis